Ableism-sensitive, self-reflective emotion work as part of inclusive teacher education - Hauser, Mandy (Frontiers in Sociology, 2025)
In this perspective article, emotions are considered as an inherent component of ableist practices, and the question is explored of how ableism-sensitive, self-reflective emotion work can be designed for inclusive teacher education. In this process, connections to the Sociology of Emotions are established, with particular emphasis on the collectivity and sociality of emotions. Within this context, self-reflective emotion work is integrated into the concept of “unlearning ableism” and argued for its implementation as a systemically oriented group process. Finally, questions regarding the design of emotion work and its implementation in a manner critical of ableism are discussed.